A ilustração e o primado da educação: as visões de António Nunes Ribeiro Sanches e do Marquês de Condorcet - Assis, Guilherme Marchiori de (2016)
The study of modernity should cover uniformly the study of the Enlightenment, season of lights, a period that used paradigmatic and analytical thinking. A historical era in which lived António Nunes Ribeiro Sanches and the Marquis de Condorcet. Both have endorsed and contributed to the scientific instruments that became known as the Republic of Letters. The transposition of thoughts and arguments overflowed in letters to different people in the case of Sanches, as well as various precepts inspired by the letters of Condorcet, brought to light the untold concept and application of public education contributions. Recent historiography about the Enlightenment has affirmed the pluralistic character and processes of composition of the ideas associated with the Enlightenment in different parts of Europe simultaneously, according to the regional peculiarities. In this context, we highlight two characters: the portuguese Antonio Ribeiro Sanches and the french Marquis de Condorcet. We analyze their differences with regard to the issue of education as a rule of the Enlightenment.